The Economic Impacts of Port Activity in Antwerp: A Disaggregated Analysis - Francois Coppens; Frederic Lagneaux; Hilde Meersman; Nathalie Sellekaerts; Eddy Van De Voorde; George Van Gastel; Ann Verhetsel (European Regional Science Association (ERSA), 2006)
The importance of ports is usually measured by indicators such as added value, employment and investment on a much aggregated level. This paper tries to define the importance of the port of Antwerp for the regional and national economy on a disaggregated level. It attempts to identify, quantify and locate the mutual relationships between the different players in the port and between these players and other industries. Finally, it proposes a method to calculate the effects of changes in port activity at a detailed level. A sector analysis is done by means of a reduced regional input-output table, through a bottom-up approach. The most important customers and suppliers of the port's key players or stakeholders are identified. A geographical analysis is feasible by using data on a disaggregated level. Each customer or supplier can be located by means of their postcode. In this way, the extent of the economic impact of the port of Antwerp is quantified.
Keywords: 330